Elimination method
, how do I begin
2x-3y=-1
-4x+6y=2

Elimination method
, how do I begin
2x-3y=-1
-4x+6y=2

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

@jamesr
@RosieF
@Chumpian

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.